More Than Words: Multimodal Transcreation in the Indonesian Localization of "Janice Goes to Chinatown" - Faiz Akbar Leksananda; Sajarwa Sajarwa; Adi Sutrisno (Journal Of Social Science (JoSS), 2026)
This research analyzes picturebook translation as multimodal transcreation, where text–image interplay (intersemiosis) serves as the central unit of analysis. It presents a case study of Janice Goes to Chinatown (Source Text, ST), set in Kolkata, India, and its Indonesian localization, Perjalanan Janice ke Pasar Pecinan (Target Text, TT). The TT publisher adapted and transmuted the work, commissioning a complete visual re-creation alongside the verbal translation. This research argues that the deliberate verbal domestication—systematically changing the setting from “Kolkata” to “Singkawang” and “rickshaws” to “delman” (a horse cart)—created an intersemiotic rupture with the original illustrations. This rupture necessitated new visuals to restore narrative coherence. Using a dual framework of Klingberg’s Cultural-Specific Items (CSIs) for the text and Kress and van Leeuwen’s Visual Grammar for the images, the analysis demonstrates how the TT achieves a new intersemiotic synergy. The visual mode, for instance, shifts from an observational “Offer” to an interactive “Demand” gaze. This act of systemic compensation exemplifies a holistic translation process, made possible by the ST’s open-source StoryWeaver platform.